Identifying the aging mechanism in multiple overdischarged LiCoO2/mesocarbon microbeads batteries. Issue 15 (1st August 2021) - Zhang, Lingling; Liu, Jilong; Du, Lei; Xu, Xing; Ma, Yulin; Qu, Bin; Fan, Peng; Yin, Geping; Yang, Fan; Zhu, Li
Abstract: Batteries can undergo overdischarge in actual applications without triggering safety issues. The interesting one is whether the battery that is overdischarged can have a second life in the following normal charge and discharge process. Herein, the effects of overdischarge are investigated using the LiCoO2 /mesocarbon microbeads (MCMB) batteries with different depth of discharge (DOD) (102% DOD, 105% DOD, and 115% DOD) for ten times; the performance and aging mechanisms of the overdischarged battery in the following normal cycling are studied mainly through the electrochemical methods, scanning electron microscopy (SEM), X-ray diffractometry (XRD), X-ray photoelectron spectroscopy (XPS), and transmission electron microscopy (TEM). For the batteries subjected to multiple shallow overdischarge (e.g., 102% DOD and 105% DOD), the aging mechanism remains unchanged, and the battery can be further used for a second life. In contrast, the multiple deep overdischarge (e.g., 115% DOD) remarkably leads to battery bulges, a drastic decrease in capacity, and a changed aging mechanism. It is noteworthy that the performance decay of LiCoO2 is deteriorated owing to the thickened Cathode-Electrolyte-Interface (CEI) and the damaged microstructure, which is different from overdischarge for one time. At the same time, the thermostability of LiCoO2 is remarkably reduced after deep overdischarge for ten times.